2008
DOI: 10.22358/jafs/66685/2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium butyrate on the growth performance, intestinal microflora and morphology of weanling pigs

Abstract: A total of 96 pigs (Duroc×Landrace×Yorkshire) weaned at day 21 with an average initial body weight of 6.68 kg were used to investigate the effects of sodium butyrate on the growth performance, intestinal microfl ora and morphology of weanling pigs. The pigs were allocated to three dietary treatments in a randomized complete block design, each treatment was replicated four times with eight pigs per replicate and the trial lasted for 30 days. The dietary treatments were: 1. basal diet, 2. basal diet + 500 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 15 publications
7
40
0
Order By: Relevance
“…Ma et al (2012) found butyrate improving antioxidative stress ability. Improved piglet performance due to butyrate supplement was found also by Lu et al (2008) and in the experiment of Miller and Slade (2006) the positive effect of butyrate was enhanced by the addition of zinc oxide. Worse results were received by Biagi et al (2007).…”
Section: Introductionmentioning
confidence: 79%
“…Ma et al (2012) found butyrate improving antioxidative stress ability. Improved piglet performance due to butyrate supplement was found also by Lu et al (2008) and in the experiment of Miller and Slade (2006) the positive effect of butyrate was enhanced by the addition of zinc oxide. Worse results were received by Biagi et al (2007).…”
Section: Introductionmentioning
confidence: 79%
“…Histological parameters reflect intestinal environment and are an indication of health status (Lu et al, 2008). Adding TA to the diets did not alter the colon crypt depth of rats.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, sodium butyrate and Yucca schidigera have received considerable attention, but most of the studies examined their influence on growth performance and the structure, function, and microbiology of the digestive tract (10,12,14,16,19). The majority of research on Yucca schidigera has been focused on odour elimination in animal production (1).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in morphology and physiology of the gastrointestinal tract had influence on metabolism and parameters of bones (4,9). Several studies have proved that the supplementation of diets with butyrate has beneficial effects on performance and digestive tract health in weaning pigs (5,10,14,32,34). However, Tonel et al (29) reported that a diet with butyrate had little effects on intestinal mucosa morphology of piglets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation